2017
DOI: 10.1186/s40104-017-0170-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of growth rate with hormone levels and myogenic gene expression profile in broilers

Abstract: BackgroundThe growth rate often varies among individual broilers of the same breed under a common management condition. To investigate whether a variation in the growth rate is associated with a difference in hormone levels and myogenic gene expression profile in broilers, a feeding trial was conducted with 10,000 newly hatched Ross 308 chicks in a commercial production facility under standard management. At 38 d of age, 30 fast-, 30 medium-, and 30 slow-growing broilers were selected among 600 healthy male in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
(33 reference statements)
2
21
0
3
Order By: Relevance
“…Jia et al (2018) reported that broiler chicks showed higher plasma IGF-1 concentration than native chicken breeds. Fast-growing broilers had higher concentrations of IGF-1 in the serum than slow-growing broilers (Xiao et al, 2017). Thus, high concentration of plasma IGF-1 may possibly be one of the causes of fast growth of broiler chickens.…”
Section: Resultsmentioning
confidence: 93%
“…Jia et al (2018) reported that broiler chicks showed higher plasma IGF-1 concentration than native chicken breeds. Fast-growing broilers had higher concentrations of IGF-1 in the serum than slow-growing broilers (Xiao et al, 2017). Thus, high concentration of plasma IGF-1 may possibly be one of the causes of fast growth of broiler chickens.…”
Section: Resultsmentioning
confidence: 93%
“…Some effects of Met concentration were observed as suboptimum Met concentrations in the basal diet fed Met‐ group reduced IGF1 signalling (GHR, IGF1) and increased protein degradation on the molecular level via UPP (MURF1) and autophagy (ATG5, BECN1/ATG6), mainly when compared to the groups fed diets with a surplus of Met (0.40% groups). IGF1 signalling is known to be connected to growth in broilers; for example, one study showed a correlation between bird weight and serum IGF concentrations as well as breast muscle IGF1 expression (Xiao et al, ). In contrast to our expectations, the Met source neither affected anabolic nor catabolic pathways in the muscle on the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR assays were performed in triplicate on an ABI Prism 7700 Sequence Detector (Applied Biosystems) using an annealing temperature of 63°C and gene-specific primers listed in Supplementary Tables S1, S2. Data were normalized to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) or 18S rRNA using the comparative ΔΔCt method as described (Xiao et al, 2017b).…”
Section: Methodsmentioning
confidence: 99%